Identifying Functional Flow Linkages Between Stream Alteration and Biological Stream Condition Indices Across California - Peek, Ryan; Irving, Katie; Yarnell, Sarah M.; Lusardi, Rob; Stein, Eric D.; Mazor, Raphael (Frontiers in Environmental Science, 2022)
Large state or regional environmental flow programs, such as the one based on the California Environmental Flows Framework (CEFF), rely on broadly applicable relationships between flow and ecology to inform management decisions. California, despite having high flow and bioassessment data density, has not established relationships between specific elements of the annual hydrograph and biological stream condition. To address this, we spatially and temporally linked USGS gage stations and biological assessment sites in California to identify suitable site pairs for comparisons of streamflow alteration with biological condition at a statewide scale. Flows were assessed using a set of functional flow metrics which provide a comprehensive way to compare alteration and seasonal variation in streamflow across different locations. Biological response was evaluated using the California Stream Condition Index (CSCI) and Algal Stream Condition Index (ASCI), which quantify biological conditions by translating benthic invertebrate or algal resources with watershed-scale environmental data into an overall measure of stream health. These indices provide a consistent statewide standard for interpreting bioassessment data and, thus, a means of quantitatively comparing stream conditions throughout the state. The results indicate that indices of biological stream condition were most closely associated with flow alteration in timing metrics such as fall pulse timing, dry-season timing, and wet season timing. Magnitude metrics such as dry-season baseflow, wet season baseflow, and the fall pulse magnitude were also important drivers of variation, and a metric of seasonality was strongly tied to biological stream conditions, particularly in snowmelt streams. Development of flow criteria under CEFF should consider that alteration to any of these seasonal flow components (e.g., dry-season baseflow, fall pulse flow, wet-season baseflow, spring recession flow) may be important in restructuring biological communities.